PENGELOLAAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL KABUPATEN TULUNGAGUNG DALAM PERSPEKTIF MAQASHID AL-SYARIAH - Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2016)
Why BAZ cannot operate optimally is due to two factors. First, as a matter of fact, this institution is just passively waiting for the zakat payers. Second, the zakat paid through this institution is limited to the zakat of income from certain offices, not from massive individual. In addition, it has been a long tradition that the Moslems do not pay their zakat fithrah through this institution. Zakat fithrah is commonly paid for the receivers’ daily consumption. Considering the problems above, some initiatives must be taken. First, institutionally BAZ must be empowered by setting up zakat picking units (UPZ) in every mosque and these units are managed professionally to serve the zakat payers. Second, the zakat must be managed and distributed to the right receivers for the productive purposes, not the consumptive purposes. Since the zakat is still distributed for the consumptive purposes, from the perspective of maqashid al syariah it can be concluded that the management of zakat so far has not yet achieved its fundamental purpose to empower and to prosper the poors and the weaks. Kata kunci: Pengelolaan, Pengumpulan dan Pendistribusian Zakat, Maqashid al-Syariah